A novel approach for positive edge consensus of nodal networks. Issue 7 (May 2020) - Cui, Yukang; Yang, Nachuan; Liu, Jason J.R.
Abstract: In this paper, we investigate the positive edge consensus of nodal networks with Luenberger observer-based dynamic output-feedback controllers. The line graph of a nodal network, which is used to model the interaction among edges, is directed and assumed to contain a spanning tree. Based on the results in graph theory and positive systems theory, positive edge consensus problem is analyzed and the protocol design condition is given. Moreover, a semi-definite programming algorithm is developed to solve the positive edge consensus problem. Compared with the recent work [24] where the nodal graph is assumed to be strongly connected and balanced, we study the positive edge consensus problem in a more general case, where the line graph is assumed to contain a spanning tree. Finally, the numerical simulations are given to verify the effectiveness of the proposed results.